Dereplication of Components Coupled with HPLC-qTOF-MS in the Active Fraction of Humulus japonicus and It's Protective Effects against Parkinson's Disease Mouse Model - Lee, Hee Ju; Dhodary, Basanta; Lee, Ju Yong; An, Jin-Pyo; Ryu, Young-Kyoung; Kim, Kyoung-Shim; Lee, Chul-Ho; Oh, Won Keun (MDPI, 2019)
Humulus japonicus is an annual plant belonging to the Cannabacea family, and it has been traditionally used to treat pulmonary tuberculosis, dysentery, chronic colitis, and hypertension. We investigated the active components against Parkinson's disease from H. japonicus fraction (HJF) using high performance liquid chromatography (HPLC) coupled with quadruple-time-of-flight mass spectroscopy (qTOF-MS) and NMR. Fourteen compounds were isolated from HJF, including one new compound, using HPLC-qTOF-MS and NMR. The major compounds of HJF were luteolin-7-O-glucoside and apigenin-7-O-glucoside, and there was approximately 12.57- and 9.68-folds increase in the contents of these flavonoids compared to those of the 70% EtOH extract. Apigenin and luteolin exhibited the strongest inhibitory effects on monoamine oxidase (MAO) B enzyme activity. In animal studies, limb-use behavior was significantly reduced by unilateral 6-OHDA lesion and ipsilateral rotations. These results indicated that oral administration of 300 mg/kg HJF resulted in the improvement of motor asymmetry and motor impairment in unilateral 6-OHDA-lesioned mice. HJF, including active components leads to an improvement of motor behavior in a Parkinson's disease mouse model.
Keywords: MONOAMINE-OXIDASE; ALZHEIMERS-DISEASE; L-DOPA; GLYCOSIDES; INHIBITION; TOXICITY; DEATH; RATS